Study on the Efficacy of “Information Platform + Self-Care Model” on the Health Status of Discharged Patients Following Vaginal Natural Orifice Transluminal Endoscopic Surgery - Tian T; Guan MJ; Liu LJ; Su XQ; Wang H; He L (Dove Medical Press, 2023)
Tian Tian,1,* Mei-Jun Guan,1,* Li-Juan Liu,1 Xiao-Qiu Su,1 Hui Wang,2 Li He1 1Department of Gynecology, Chengdu Women's and Children's Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, 611731, People's Republic of China; 2Department of Gynecological Day Surgery, Chengdu Women's and Children's Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, 611731, People's Republic of China*These authors contributed equally to this workCorrespondence: Li He, Department of Gynecology, Chengdu Women's and Children's Central Hospital, School of Medicine, University of Electronic Science and Technology of China, No. 1617 of Riyue Anenue, Qingyang District, Chengdu, 611731, People's Republic of China, Tel +86 13881782966, Email helihlop0@126.comObjective: To discuss the impact of the "information platform + self-care model" on the health status of discharged patients following vaginal natural orifice transluminal endoscopic surgery (vNOTES).Methods: Patients underwent vNOTES at a tertiary specialized women's and children's hospital in Chengdu. They were randomly assigned to one of two groups-the intervention group (29 patients) and the control group (29 patients). The control group received standard education after discharge, while the intervention group received guidance based on an "information platform + self-care model" on discharge; a questionnaire survey was conducted for both groups one month after discharge.Results: The quality of life score in the intervention group was higher than that in the control group, and the difference was statistically significant (P < 0.05); the scores of the intervention group on dimensions such as vitality, general health perceptions, physical role functioning, social role functioning, emotional role functioning, and mental health, except for physical functioning (Z =  0.034, P =  0.973) and bodily pain (Z =  1.470, P =  0.141), were higher than those in the control group one month after discharge, and the difference was statistically significant (P